The New Immigrant Survey Round 1 (NIS-2003-1), United States, 2003-2004 (Public and Restricted-Use Version 1) - Jasso, Guillermina ([Verlag nicht ermittelbar], 2022)
The New Immigrant Survey (NIS) was a nationally representative, longitudinal study of new legal immigrants to the United States and their children. The sampling frame was based on the electronic administrative records compiled for new legal permanent residents (LPRs) by the U.S. government (via, formerly, the U.S. Immigration and Naturalization Service (INS) and now its successor agencies, the U.S. Citizenship and Immigration Services (USCIS) and the Office of Immigration Statistics (OIS)). The sample was drawn from new legal immigrants during May through November of 2003. The geographic sampling design took advantage of the natural clustering of immigrants. It included all top 85 Metropolitan Statistical Areas (MSAs) and all top 38 counties, plus a random sample of MSAs and counties. The baseline survey (ICPSR 38031) was conducted from June 2003 to June 2004 and yielded data on: 8,573 Adult Sample respondents, 810 sponsor-parents of the Sampled Child, 4,915 spouses, and 1,072 children aged 8-12. Interviews were conducted in the respondents' language of choice. The Round 1 questionnaire that were used in social-demographic-migration surveys around the world as well as the major U.S. longitudinal surveys were reviewed in order to achieve comparability.